2020
DOI: 10.1038/s41598-020-71240-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and analysis of GRAS transcription factors in the bottle gourd genome

Abstract: GRAS genes belong to the plant-specific transcription factors (TF's) family that are known to be involved in plant growth and development. In this study, we have identified 37 genes from the bottle gourd genome that encodes for GRAS TF's. Except for the SCLA, we were able to identify at least one gene from each of the 17 subfamilies. Gene structure and chromosomal analysis showed that maximum seven genes are present on Chr7 followed by six genes on Chr1. The subcellular location analysis revealed that most of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 51 publications
2
17
0
1
Order By: Relevance
“…The GRAS gene family has been extensively studied in many plant species: once the GRAS genes of the model organisms Arabidopsis and rice were identified [ 6 8 ], these genes could be more widely explored in many other species. This family has been identified and analyzed at the whole-genome level in Solanum lycopersicum [ 43 ], Vitis vinifera [ 44 ], castor bean [ 45 ], Malus domestica [ 46 ], Zea mays [ 47 ], Camellia sinensis [ 48 ], Gossypium hirsutum [ 49 ], Capsicum annuum [ 50 ], Dendrobium catenatum [ 51 ], Juglans regia [ 52 ], Fagopyrum tataricum [ 53 ], Brassica napu s [ 54 ], Citrus sinensis [ 55 ], Hordeum vulgare [ 56 ], Manihot esculenta [ 57 ], Lagenaria siceraria [ 58 ] and others. However, knowledge of the GRAS gene family in S. bicolor is still very limited.…”
Section: Introductionmentioning
confidence: 99%
“…The GRAS gene family has been extensively studied in many plant species: once the GRAS genes of the model organisms Arabidopsis and rice were identified [ 6 8 ], these genes could be more widely explored in many other species. This family has been identified and analyzed at the whole-genome level in Solanum lycopersicum [ 43 ], Vitis vinifera [ 44 ], castor bean [ 45 ], Malus domestica [ 46 ], Zea mays [ 47 ], Camellia sinensis [ 48 ], Gossypium hirsutum [ 49 ], Capsicum annuum [ 50 ], Dendrobium catenatum [ 51 ], Juglans regia [ 52 ], Fagopyrum tataricum [ 53 ], Brassica napu s [ 54 ], Citrus sinensis [ 55 ], Hordeum vulgare [ 56 ], Manihot esculenta [ 57 ], Lagenaria siceraria [ 58 ] and others. However, knowledge of the GRAS gene family in S. bicolor is still very limited.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that these motifs interact with the GA-bound receptor GA-2017), walnut (Quan et al, 2019) and clover (Zhang et al, 2017). However, in other plant species, the number of subfamilies is higher, for instance, 13 subfamilies were identified in the case of Populus trichocarpa (Liu and Widmer, 2014), Camellia sinensis (Wang et al, 2018) and castor bean (Xu et al, 2016) and 16 subfamilies were identified in bottle gourd (Sidhu et al, 2020).…”
Section: Structural Features Of the Gras Proteinsmentioning
confidence: 99%
“…Eudicot 21 08 (Chen et al, 2015) Oryza sativa (rice) Poaceae Monocot (Tian et al, 2004) Panax ginseng (ginseng) Araliaceae Eudicot (Wang et al, 2020b) Physcomitrella patens (moss) Funariaceae Monocot 13 (Wu et al, 2014) Populus tremula (populus) et al, 2008), Amborella trichopoda (Albert et al, 2013), Capsicum annum , Coffea canephora (Denoeud et al, 2014), Fragaria vesca (Chen et al, 2019a), Gossypium hirsutum (Zhang et al, 2018), Lagenaria siceraria (Sidhu et al, 2020), Musa acuminate (D'Hont et al, 2012), Oryza sativa (Tian et al, 2004), Phoenix dactylifera (Al-Mssallem et al, 2013), Theobroma cacao (Argout et al, 2011) and Vitis vinifera (Grimplet et al, 2016). MEGA X aligned the GRAS protein sequences (581) of the 12 plant species with the MUSCLE method.…”
Section: Solanaceaementioning
confidence: 99%
“…The GRAS proteins of the four species were grouped into 17 different subfamilies. Out of 17, 16 subfamilies (PAT1, LISCL, SCL3, SCL32, DELLA, SCR, DLT, HAM, LAS, SCL4/7, SHR, SCLA, RAD1, RAM1, NSP1, NSP2) were designated according to previous studies (Cenci and Rouard, 2017;Sidhu et al, 2020;Tian et al, 2004). A remaining Rosaceae-speci c subfamily (contains only rose and strawberry GRAS proteins) which is not grouped into any of the earlier reported subfamilies was named as Rc2 subfamily.…”
Section: Phylogenetic and Syntenic Analyses Of Gras Genesmentioning
confidence: 99%
“…In Arabidopsis and rice, the GRAS genes were grouped into eight subfamilies, including-(i) DELLA, (ii) Hairy meristem(HAM), (iii) Light signaling through interactions light-responsive transcription factor PIFs (LISCL), (iv) Lateral suppressor (LS or LAS), (v) Phytochrome A signal transduction1 (PAT1), (vi) Scarecrow-like3 SCL3, (vii) SCR, and (viii) short-root (SHR) (Lee et al, 2008;Tian et al, 2004). However, in other plant species, the number of subfamilies were reported higher than 8; for instance, 13 subfamilies were identi ed in the case of Populus trichocarpa (Liu and Widmer, 2014), Camellia sinensis (Wang et al, 2018) and castor bean (Xu et al, 2016), 14 subfamilies were identi ed in strawberry (Chen et al, 2019) and cotton (Zhang et al, 2018) and 16 subfamilies were identi ed in bottle gourd (Sidhu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%